PERANAN ORANGTUA TERHADAP PENDIDIKAN AKHLAK ANAK USIA DINI DI DESA PENDA ASAM KECAMATAN DUSUN SELATAN KABUPATEN BARITO SELATAN - Rina, Asma; Gazali, Achmad (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2023)
The role of parents in the moral education of early childhood is an effort by parents to make people who have faith and devotion to God Almighty, have noble character, respect and love the parents who have educated and cared for them, which can be achieved as expected in Penda Asam Village, District. South Hamlet, South Barito Regency. This research examines the role of parents in the moral education of early childhood in Penda Asam Village, Dusun Selatan District, South Barito Regency and the factors that influence the role of parents in the moral education of early childhood in Penda Asam Village, Dusun Selatan District, South Barito Regency. This research uses a quantitative descriptive approach with the type of field research and is supported by references related to the themes discussed in this research. The population in this study were all parents in Penda Asam Village, Dusun Selatan District, South Barito Regency who had 100 young children. The sample for this study consisted of the existing population, 20% of which was used as the sample. There are 20 people in all. To obtain field data, interview and documentary techniques and questionnaires were used. The results of this research conclude that the role of parents in the moral education of early childhood in Penda Asam Village, Dusun Selatan District, South Barito Regency is quite good. The factors that influence the role of parents in early childhood moral education in Penda Asam Village, Dusun Selatan District, South Barito Regency are educational background, time available for children, parents' family economy and family size